2013
DOI: 10.4187/respcare.01685
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behaviors of Flutter VRP1, Shaker, and Acapella Devices

Abstract: The Flutter VRP1 and Shaker devices had a similar performance to that of Acapella in many aspects, except for PEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 17 publications
0
21
0
6
Order By: Relevance
“…Every session lasted 30 minutes and every patient had a treatment twice per day (morning and late afternoon). Chest Physiotherapy (CPT) consisted of a group of respiratory physiotherapy techniques like, slow expiratory with glottis opened in lateral position (ELTGOL) [24], positive expiratory pressure (PEP) mask [25] or PEP bottle [26] and vibratory positive expiratory pressure therapy system [27] (Acapella choice, Smiths Medical, England). Every session lasted 45 minutes and every patient had a treatment twice per day (morning and late afternoon).…”
Section: Methodsmentioning
confidence: 99%
“…Every session lasted 30 minutes and every patient had a treatment twice per day (morning and late afternoon). Chest Physiotherapy (CPT) consisted of a group of respiratory physiotherapy techniques like, slow expiratory with glottis opened in lateral position (ELTGOL) [24], positive expiratory pressure (PEP) mask [25] or PEP bottle [26] and vibratory positive expiratory pressure therapy system [27] (Acapella choice, Smiths Medical, England). Every session lasted 45 minutes and every patient had a treatment twice per day (morning and late afternoon).…”
Section: Methodsmentioning
confidence: 99%
“…72, 73 The Lung Flute is a small self-powered handheld audio device that produces a low frequency acoustic wave with moderately vigorous exhalation, rather than oscillatory back pressure, to increase mucus clearance. 74 The majority of patients can manage their chest clearance without requiring devices, but these may be helpful as adjuncts under the supervision of specialist chest physiotherapists.…”
Section: Overall Goals Of Treatmentmentioning
confidence: 99%
“…The authors concluded that the Flutter, VRP1 and Shaker devices had a similar performance to that of Acapella in many aspects, except for PEP [9]. It was found that there were significant difference in FVC, FEV1, also (PaO2) and carbon dioxide pressure (PaCO2) in group-A who received positive expiratory pressure breathing (PEPB) plus traditional physical therapy program (TPTP) than group-B who received TPTP only after 4 weeks [10].…”
Section: Discussionmentioning
confidence: 99%